2000
DOI: 10.1017/s0967199400000770
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of 6-DMAP, olomoucine and roscovitine on Xenopus oocytes and eggs

Abstract: The effects of the new cyclin-dependent kinase inhibitors, roscovitine and olomoucine, on oocytes and eggs of Xenopus laevis were investigated and compared with those of 6-dimethylamino purine (6-DMAP). The inhibitory properties of 6-DMAP, olomoucine and roscovitine towards p34cdc2-cyclin B isolated from Xenopus eggs revealed K-IC50 values of 300, 40 and 10 μM respectively. The three compounds inhibited progesterone-induced maturation with M-IC50 values of 200, 100 and 20 μM. These values were consistent with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 35 publications
0
13
1
1
Order By: Relevance
“…Roscovitine, as an inhibitor of MPF, has been shown to be an effective activation agent in rhesus oocytes (Mitalipov et al 2001). We chose injection of roscovitine rather than culture with roscovitine as an activation treatment in this study because injection was reported to be the more effective treatment in Xenopus (Flament et al 2000), and injection was simply performed in our system by addition of roscovitine to the sperm extract solution. However, this treatment did not increase blastocyst development rates, and resulted in a conceptus that developed abnormally in early gestation and was lost before 114 days.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Roscovitine, as an inhibitor of MPF, has been shown to be an effective activation agent in rhesus oocytes (Mitalipov et al 2001). We chose injection of roscovitine rather than culture with roscovitine as an activation treatment in this study because injection was reported to be the more effective treatment in Xenopus (Flament et al 2000), and injection was simply performed in our system by addition of roscovitine to the sperm extract solution. However, this treatment did not increase blastocyst development rates, and resulted in a conceptus that developed abnormally in early gestation and was lost before 114 days.…”
Section: Discussionmentioning
confidence: 99%
“…Roscovitine, an inhibitor of ATP binding to MPF, has been used via this activity to induce activation of oocytes, either parthenogenetically or after NT (Mitalipov et al 2001). In Xenopus, microinjection of roscovitine was found to be more effective for oocyte activation than was incubation in roscovitine-containing medium (Flament et al 2000). To our knowledge, the effect of injection of roscovitine on oocyte activation in mammalian species has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Completion of meiosis is attested by the extrusion of the second polar body and pronucleus formation. Following fertilization as well as following parthenogenetic activation, MPF drops within five minutes while MAPK remains active for 30 minutes before decreasing [22], [23]. Inactivation of MPF is mainly due to the degragation of the Cyclin B whereas inactivation of MAPK reflects the degradation of its upstream activator Mos [24].…”
Section: Introductionmentioning
confidence: 99%
“…In Xenopus oocytes, Mos had appeared as the best candidate for a MPF-regulated stimulator of the MAPK activation during meiosis, although Mos-independent mechanisms cannot be excluded. Indeed, if the first MPF activation burst at metaphase I is impaired by chemical inhibitors such as roscovitine and olomoucine (Flament et al, 2000) or through the use of Cdc2 negative mutants or Cdc2 inactivating antibodies (Nebreda et al, 1995), no MAPK activation is observed in Xenopus oocytes. Oligonucleotide strategies targeting cyclin B have also been employed to address the role of MPF during meiosis, but failed to prevent the activation peak at meiosis I because the latter relies on cyclins associated to Cdc2 under an inactive stored stock of MPF (called pre-MPF) and is not dependent upon cyclin B synthesis.…”
mentioning
confidence: 99%